Dasa Sudra slavery Vol.I Part II - Sharad Patil; PATIL (Sharad) (Pune Sugawa Prakashana, 1991)
Studies in the origins of Indian slavery and Feudalism and their philosopies
Keywords: Post Indus Theocratic Monarchy; Oligarchy; Philosophies of the Slave Era; Feudal Revolution